The role of tax authorities in public acceptance of indirect tax in Malaysia / Nur Erma Suryani Mohd Jamel ... [et al.] - Mohd Jamel, Nur Erma Suryani; Hamid, Nadiah Abdul; Mohd Zawawi, Siti Noor Hayati; Othman, Rani Diana; Sulaiman, Saliza (Universiti Teknologi MARA, Perlis, 2021)
From 1st September 2018, the reimplementation of the Sales and Service Tax (SST) was due to take effect replacing the Goods and Service Tax (GST). The nation opposed GST as they argued that it was an added burden to their already high living cost. As the government had to find an alternative source to collect tax revenue, the best solution will be implementing the Sales and Services Tax. In contrast to GST which was carried on a value-added concept, this new charge is only imposed at manufacturer stages. Therefore, the supply chain would result in higher charges, shifting from manufacturers to retailers and consumers. Although the Consumer Price Index (CPI) basket is taxable, it is just 38 per cent of the total products and services. According to the National Worry Index conducted by Emir Research Malaysia, most respondents believe that Sales and Services Tax failed to reduce the prices of goods and services. Hence, acceptance is vital to ensure the success of indirect tax. Therefore, the present study aims to examine tax authorities’ role and public acceptance of SST in Malaysia. Data from 180 people living in Klang Valley were collected through a survey. To examine calculation and structural models, the Partial Least Square - Structural Equation Model (PLS-SEM) approach was adopted. This study’s findings suggested that tax authorities’ effectiveness, namely, the Royal Malaysian Customs Department (RMCD) and the Ministry of Domestic Trade and Consumers Affairs (KPDNHEP), influenced public acceptance. Furthermore, the adoption of SST requires tax transparency and public confidence in the government. The understanding of the government, in particular, is a critical problem because, as an acknowledgement of the SST, it goes beyond the direct range of the taxation authorities. The public should perceive that tax authorities are effective, transparent, and trustworthy in executing indirect tax. Malaysians would be more accepting if the government declares the revenues from the tax obtained, as well as spending the tax income wisely on public amenities. These findings have important implications for the government to understand public acceptance in SST. Transparency will enhance public confidence in the government. Malaysians have to perceive that the Malaysian tax authorities are useful and the tax must be transparent to give their full trust to the government.